Moral Value of Fantasy Literary: A Critical Discourse - Mega Febriani Sya; Novi Anoegrajekti; Ratna Dewanti (Indonesian Journal of Social Research (IJSR), 2023)
Fantasy literature has grown, diversified, and become famous in recent decades. One such phenomenon is Harry Potter, which has a readership base from all over the world to make this fantasy literary novel one of the world's most famous cultures. However, it is crucial to know how popular culture influences moral practices in its readers, so it is necessary to identify what kind of moral representation appears in the text. This study aims to examine the representation of ideology through moral conceptions. Fairclough's critical discourse analysis was applied to discover the reality behind the text of the Harry Potter novels and The Philosopher's Stone. The finding of this study is that there are ten discourses of moral representation related to morality in education, morality in private and public interactions, morality formed based on social strata, and morality in the view of norms and ethics. Morality is not only about good and bad but how it affects the order of life in social life, even though it is represented in an unlimited imagination.Fantasy literature has grown, diversified, and become famous in recent decades. One such phenomenon is Harry Potter, which has a readership base from all over the world to make this fantasy literary novel one of the world's most famous cultures. However, it is crucial to know how popular culture influences moral practices in its readers, so it is necessary to identify what kind of moral representation appears in the text. This study aims to examine the representation of ideology through moral conceptions. Fairclough's critical discourse analysis was applied to discover the reality behind the text of the Harry Potter novels and The Philosopher's Stone. The finding of this study is that there are ten discourses of moral representation related to morality in education, morality in private and public interactions, morality formed based on social strata, and morality in the view of norms and ethics. Morality is not only about good and bad but how it affects the order of life in social life, even though it is represented in an unlimited imagination.